Structure of unstable nuclei from nuclear moments and β decays - Asahi, K; Uchida, M; Shimada, K; Nagae, D; Kameda, D; Ueno, H; Yoshimi, A; Takemura, M; Arai, T; Takase, K; Inoue, T; Kawamura, H; et al. (Journal of physics. Conference series, 2006)
The structure of neutron-rich nuclei around the N 20 magic number is studied through the measurements of static electromagnetic moments. Recent data on the magnetic dipole moments and electric quadrupole moments for neutron-rich Al isotopes are discussed to clarify whether the emergence of a strong deformation reported for Z 10−12 nuclei in this region might happen also in these Z 13 nuclei. Possibility to study the nuclear structure via the β transition matrix elements is also discussed.